Biodegradation and Biotransformation of Indole: Advances and Perspectives - Ma, Qiao; Zhang, Xuwang; Qu, Yuanyuan (Frontiers in Microbiology, 2018)
Indole is long regarded as a typical N-heterocyclic aromatic pollutant in industrial and agricultural wastewater, and recently it has been identified as a versatile signaling molecule with wide environmental distributions. An exponentially growing number of researches have been reported on indole due to its significant roles in bacterial physiology, pathogenesis, animal behavior and human diseases. From the viewpoint of both environmental bioremediation and biological studies, the researches on metabolism and fates of indole are important to realize environmental treatment and illuminate its biological function. Indole can be produced from tryptophan by tryptophanase in many bacterial species. Meanwhile, various bacterial strains have obtained the ability to transform and degrade indole. The characteristics and pathways for indole degradation have been investigated for a century, and the functional genes for indole aerobic degradation have also been uncovered recently. Interestingly, many oxygenases have proven to be able to oxidize indole to indigo, and this historic and motivating case for biological applications has attracted intensive attention for decades. Herein, the bacteria, enzymes and pathways for indole production, biodegradation and biotransformation are systematically summarized, and the future researches on indole-microbe interactions are also prospected.